2019
DOI: 10.1016/j.fsi.2019.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Haematological and intestinal health parameters of rainbow trout are influenced by dietary live yeast and increased water temperature

Abstract: Live yeast may be a sustainable protein source in salmonid diets while exhibiting a probiotic effect to counteract environmental stressors, such as increased water temperature that is being exacerbated by climate change. The objective of this study was to evaluate the effects of feeding a high dietary inclusion of live yeast and increased water temperature on growth, haematological and intestinal physiology of rainbow trout. For six weeks, 129 g fish in 16 tanks (n=4) were fed either a diet based on fishmeal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 98 publications
(141 reference statements)
4
22
1
Order By: Relevance
“…The rainbow trout ( Oncorhynchus mykiss ) is an artificially cultivated cold-water fish that is very sensitive to changes in water temperature. When the water temperature exceeds 18°C, the rainbow trout (adult fish) has a stress response, which may lead to reduced food intake, abnormal behavior, growth inhibition, and even death ( Wendelaar, 1997 ; Huyben et al, 2019 ; Zhou et al, 2019 ). The gut is particularly sensitive to any type of stress, including heat stress ( Sundh et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The rainbow trout ( Oncorhynchus mykiss ) is an artificially cultivated cold-water fish that is very sensitive to changes in water temperature. When the water temperature exceeds 18°C, the rainbow trout (adult fish) has a stress response, which may lead to reduced food intake, abnormal behavior, growth inhibition, and even death ( Wendelaar, 1997 ; Huyben et al, 2019 ; Zhou et al, 2019 ). The gut is particularly sensitive to any type of stress, including heat stress ( Sundh et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…As other studies demonstrated, many biotic and abiotic factors can affect blood parameters in fish [ 22 , 38 , 39 ]. Seasonal differences in blood biomarkers may occur due to alterations in water physicochemical parameters, such as differences in temperature, dissolved oxygen concentration, rainfall, river deposits, decomposing organic matter, dissolved solids, etc.…”
Section: Discussionmentioning
confidence: 98%
“…Seasonal differences in blood biomarkers may occur due to alterations in water physicochemical parameters, such as differences in temperature, dissolved oxygen concentration, rainfall, river deposits, decomposing organic matter, dissolved solids, etc. During summer, stress due to improper water temperatures and low dissolved oxygen levels is an increasingly common issue, severely affecting the growth performances of rainbow trout [ 6 , 22 ]. The data obtained in our study regarding the physicochemical parameters of the water in the three farms are in accordance with other studies [ 40 , 41 , 42 , 43 , 44 ], which follow the environmental parameters necessary for the normal development of rainbow trout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Huyben et al . (2019) documented that the inclusion of live yeast, Saccharomyces cerevisiae (by replacing 40% of fishmeal protein) in rainbow trout feed did not counteract the adverse effects of high‐temperature stress. Several researchers opinioned that the richness of nucleotides, β‐glucans, mannan oligosaccharides, and chitin makes yeast a potential immunomodulator and stress mitigator (Gong et al .…”
Section: Stress Mitigation Through Dietary Additives/nutraceuticalsmentioning
confidence: 99%